Comparative Phytochemical Profiling and Biological Activities in the Flowers and Stalks of Tulbaghia violacea - Maleka, Gontse; Oyerinde, Rebecca Opeyemi; Risenga, Ida Masana (Borneo Journal of Pharmacy, 2024)
Tulbaghia violacea is indigenous to Southern Africa and has been used extensively in traditional medicine in this region. Extensive research has been documented on the bioactive compounds found in the leaves and roots but not in the flowers and stalks. Thus, this study assessed the phytochemical profile and biological activities in the flowers and stalks of T. violacea. Methanolic and aqueous extracts of the air and freeze-dried T. violacea were screened for phytochemicals, and then antioxidant and antibacterial assays were performed. Phytochemicals such as phenols, tannins, flavonoids, coumarins, and terpenoids are present in either of the tested plant parts. The flowers contain most of the phytochemicals being tested and a higher total phenolic, tannin, and proanthocyanidin content than the stalks. The flowers exhibit the strongest scavenging activity against 2,2-diphenylpicryhydrazyl radicals and metal oxidants. The hydrogen peroxide scavenging activities show that the aqueous flower extracts have a higher radical scavenging activity than stalks. In contrast, the methanolic stalk extracts have a higher antioxidant activity than the flowers. Antibacterial activity is only exhibited in the flowers, showing resistant and intermediate inhibition zones of Escherichia coli and Staphylococcus aureus growth, respectively. This study validates the use of T. violacea in traditional medicine, and these results are significant for conserving the species as specific plant parts can be harvested to treat specific ailments. This study suggests the potential application of T. violacea, particularly the flowers and stalks, in the pharmaceutical and cosmetic sectors.